Intrauterine Fetal Death With Vanishing Gastroschisis and Post Mortem Examination Findings. (April 2017) - Jolley, Alexandra Frances; Beare, Elizabeth Jane; Granger, Jeremy; Cord-Udy, Catherine Lucy; Muller, Peter; Moore, Lynette
We present a severe case of vanishing gastroschisis resulting in intrauterine death with post mortem examination findings. Gastroschisis is defined as a full thickness paraumbilical abdominal wall defect associated with evisceration of fetal intestine. It is almost always right-sided. Vanishing gastroschisis is an extremely rare form of gastroschisis that results in short bowel syndrome due to exteriorized bowel disconnected from the lumen of the rest of the bowel proximally as well as distally in association with partial or complete closure of the abdominal wall. This case is only the second published case of vanishing gastroschisis resulting in intrauterine fetal death including post mortem examination findings. It highlights the importance of being aware of this rare form of gastroschisis and provides insights regarding pathogenesis, ultrasound surveillance, and antenatal counseling.